Potensi Trichoderma sp. Indigenus Gorontalo sebagai Dekomposer Limbah Tanaman Jagung - Rida Iswati; Abdul Latief Abadi; Luqman Qurata Aini; Soemarno Soemarno; Asnawi Asnawi; Siska Irhamnawati Pulogu; Sofyan Sudirman Rudin (Jurnal Ilmu Pertanian Indonesia, 2024)
Using decomposers of fungi to increase the composting process is very necessary. The research aims to determine the potential of Trichoderma sp. Gorontalo local isolate as a decomposer of maize stover. The research was carried out from November 2022‒January 2023 at the Biological Agents Laboratory, Agricultural Plant Protection Center, Gorontalo Province Agricultural Department. This research determined the ability of six isolates of Trichoderma, namely TZ11DI1 (T. asperellum), TZ21BN2 (T. breviconvenctum), TZ21BT1 (T. virens), TZ12PO1 (T. ghanence), TZ21DU1 (T. reesei), TZ21LU1 (T. dorothopsis), and control (EM4) to produce cellulase and as a maize stover decomposer. The parameters observed were the clear zone in the isolate growing media as well as the physical and chemical characteristics of the compost produced. The results showed that Trichoderma isolates produced cellulase and potential as a decomposer for maize stover, as indicated by the ability to increase NPK nutrient levels and reduce the C/N ratio of maize stover compost. Keywords: compost, decomposer, maize stover, Trichoderma